Fã-ativismo na telenovela em família - Arab, Analú Bernasconi (Universidade Federal de São Carlos, 2015)
If fan-activism actions have already been related to fan engagement in order to achieve a result in relation to their favorite media content, nowadays they are emerging from real-world concernings through consumption bias to be more active in terms of civil rights and political participation. In Clarina fandom it was possible to notice these two perspectives in a fusion, in which fans mobilized so that Clara and Marina´s romance was not discarded from the soap opera Em família by the channel network Rede Globo. Simultaneously, fans wanted the romance could be expressed throughout affection displaying and intimacy just as naturally and highlighted as a heterosexual couple on a soup opera. The fan activists of Clarina fandom appropriately demanded from Rede Globo their right to take part in their culture in a way that has never been seen before in Brazilian soap opera production. The achievement of the kiss and Clara and Marina´s marriage represented their victory against prejudice and the legitimation of their civil rights considering what they have called "Brazilian family". If the fan-activism of Clarina fandom was so expressive, it is because Brazilian soap operas still have significant cultural representativeness and its increasing power to approach polemic themes from daily social issues can transform soap operas into discussion areas about civil, religious, political and moral conflicts in the current convergence culture. However, in order to evaluate the performance of a contemporary soap opera, it is necessary to take into account not only its audience in the broadcast format, but also in the multiple media platforms and the power of engagement that it promotes.
Keywords: Telenovela brasileira; Homossexualidade; Fã-ativismo; Fandom Clarina; Brazilian soap opera; Homosexuality; Fan-activism; LINGUISTICA, LETRAS E ARTES::ARTES::ARTES DO VIDEO